Risk of Serious Skin Rash with Antiepileptic Drugs - J Gordon Millichap (Pediatric Neurology Briefs)
The risk of serious cutaneous reactions during the introduction of antiepileptic drug treatments was evaluated by a cohort study of prescription and hospitalization files for the Province of Saskatchewan, Canada, conducted at Worldwide Epidemiology, Glaxo Wellcome, Research Trangle Park, NC; and the Department of Dermatology, Beth Israel Hospital, Harvard Medical School, Boston, MA.